THE URBAN EVOLUTION OUAD EL HAD: FROM A MINOR URBAN EXTENSION TO AN INFAMOUS AND ILLICIT NEIGHBORHOOD - Aibeche Roufeida,; Farid Dalel,; Bakiri Hadia,; Bouleksa Leila,; Naidja Amina, (International Journal of Innovative Technologies in Social Science, 2024)
Informal housing represents a complex phenomenon with far-reaching implications for urban development and social equity, it is characterized by its spontaneous and unauthorized nature, it has emerged as a significant phenomenon in urban areas worldwide and usually arises a multitude of socio-economic challenges such as rapid urbanization, poverty, and as in our case, rural migration, Therefore, understanding the spatial evolution of informal settlements is crucial for designing more equitable and sustainable living environments.That was the case of “Ouad El Had”, a neighborhood that may be considered as one of the focal points in metropolis of Constantine, informal housing started as an extension, an illicit urbanization due to rural-to-urban migration led to the perpetuation of informal settlements on what was in that time the outskirts of city, Nowadays, housing shortages caused the proliferation of informal settlements, those settlements presented a chance to obtain a house in the social housing program given by the government leading it to get repopulated every time and after several attempts to evacuate the entire zone starting from 2012 to this actual day.Our paper offers an in-depth analysis of the spatial and temporal evolution to the informal housing situated in the neighborhood “Cité des Fréres Abbas” (Ouad El Had) and its evolution within urban and social contexts with the objective of understanding the complex case of this neighborhood that led to its repopulation after every evacuation or displacement and identifying the urban model generated of during this process.